(1-7i)-(1-5i)=

Simple and best practice solution for (1-7i)-(1-5i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1-7i)-(1-5i)= equation:


Simplifying
(1 + -7i) + -1(1 + -5i) = 0

Remove parenthesis around (1 + -7i)
1 + -7i + -1(1 + -5i) = 0
1 + -7i + (1 * -1 + -5i * -1) = 0
1 + -7i + (-1 + 5i) = 0

Reorder the terms:
1 + -1 + -7i + 5i = 0

Combine like terms: 1 + -1 = 0
0 + -7i + 5i = 0
-7i + 5i = 0

Combine like terms: -7i + 5i = -2i
-2i = 0

Solving
-2i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Divide each side by '-2'.
i = 0

Simplifying
i = 0

See similar equations:

| 5t-3=7 | | X/18+1=-3 | | (a^8b^2)(a^6b^8)= | | 4x-6x=x-9 | | b=85+(10+7)w | | 10x/5x-1=5+2/5x-1 | | 7x-(-4)=54 | | 7(r-1)-3=2r+5 | | -7(n+7)=4n-16 | | 4x+9-x= | | ln(4-2x)+ln(9-3x)=21n(x+1) | | 2(9x+5)=-26 | | 3z+1/4=4z+7/4 | | 86=-70+13x | | 2b+4028=51514 | | 17+-5= | | -2(4x+2)=12 | | 5x-x+2=2x+2x+2 | | 2(2x+30)+4x=360 | | (2-4i)+(1-4i)= | | 0=x^2-1 | | 11b-2b= | | 13+(-6n)+(-15)+(-5n)= | | 1.1x+-5.4=-10 | | 5/9x=5/3 | | 1/5x+2/5x+3=18 | | (5-8*2)+12=-54 | | 11-2(3m-10)=6(4-m) | | x/-3+2=7 | | 10x=25x-3 | | 2x+3(x+7)=-29 | | -5=m-6+6 |

Equations solver categories